Research hotspots and trend analysis of per- and polyfluoroalkyl substances in the environmental field based on bibliometric analysis - Fang Yang; Zhonghong Li (Emerging Contaminants)
Per- and polyfluoroalkyl substances (PFASs) have garnered significant attention as emerging contaminants (ECs) due to their concerning implications for ecological systems and human well-being, as well as their exhibited sustained environmental persistence, long-range migration capabilities, and bioaccumulation characteristics. To comprehensively and systematically understand the research hotspot and cutting-edge trends related to PFASs in the environmental field, a quantitative investigation was conducted based on 7735 PFAS-related articles extracted from the Web of Science Core Collection (WOSCC) from 2000 to 2023. The assessment involved trend of publication, prominent research contributors (countries, authors, and institutions) and influential journals. The results indicated a marked increase in the number of publications focused on environmentally-oriented PFASs since 2014, with these publications constituting approximately 83.89 % of the total body of literature on this topic. China and the USA emerged as the foremost contributors in this field. The preeminent journals included Environmental Science & Technology, Chemosphere, and Science of the Total Environment. Keyword frequency, co-occurrence network, and burst analysis delineated PFASs' research in the environmental field primarily focused on environmental monitoring, toxic effects, and the ultimate destinations and degradation pathways of the PFASs. It is anticipated that future research will focus on investigating the toxic mechanisms of PFASs' impacts on human health and on developing techniques to remove PFASs from drinking water. This study provided a comprehensive overview of the extant literature, granting researchers an enriched understanding of PFASs’ research progress and offering valuable insights regarding potential avenues for further investigation.